CORRELATION BETWEENREADING HABIT AND VOCABULARY MASTERY - Maya Angella Basampe; Abdul Kamaruddin; Maf'ulah Maf'ulah (e-Journal of ELTS (English Language Teaching Society), 2022)
The aim of this research is to find out if there is any significant correlation between reading habit and vocabulary mastery of grade eight students at SMPN 2 Lembo Raya. The researchers used correlation research design. The sample of this research was the eighth grade students of SMPN 2 Lembo Raya that consisted of 50 students. The instruments of data collection were questionnaire and vocabulary test. The technique of data analysis used Pearson Product Moment. Based on the data analysis, the result shows that the rxy was -0.077 and the t-obtained was 0.597. It means that there is no significant correlation between reading habit and vocabulary mastery because students’ reading habit has no impact on their vocabulary mastery. The reading habit that they have only in reading Indonesia text books while this research focus on English